Concomitant hypertension is associated with abnormal left ventricular geometry and lower systolic myocardial function in overweight participants: the FAT associated CardiOvasculaR dysfunction study. Issue 6 (June 2020) - Herfindal, Bertina; Gerdts, Eva; Kringeland, Ester Anne; Saeed, Sahrai; Midtbø, Helga; Halland, Hilde
Abstract : Objective: We studied the impact of concomitant hypertension on left ventricular (LV) systolic myocardial function and geometry in apparently healthy women and men with increased BMI. Material and methods: We performed a cross-sectional analysis of 535 participants (59% women) with BMI greater than 27 kg/m 2 without known cardiovascular disease enrolled in the FAT associated CardiOvasculaR dysfunction (FATCOR) study. Hypertension was defined as use of antihypertensive treatment or elevated 24-h ambulatory blood pressure. Abnormal LV geometry was identified as increased relative wall thickness and/or LV mass index. Systolic myocardial function was assessed by midwall shortening (MWS) and speckle tracking peak global longitudinal strain (GLS). Results: Hypertensive participants were older (49 vs. 46 years), had higher BMI and waist circumference, higher prevalences of diabetes and abnormal LV geometry (29 vs. 16%), and lower GLS (−19 vs. −20%) and MWS (16.3 vs. 17.1%) compared with normotensive participants (all P < 0.01). In multivariable linear regression analyses, hypertension was associated with lower GLS ( β =0.11, P = 0.035) and lower MWS ( β =0.09, P = 0.029) independent of sex, diabetes, LV hypertrophy, ejection fraction, and waist circumference. Hypertension was also associated with presence of abnormal LV geometry [odds ratio 1.74 (95% confidence interval 1.04–2.89), P = 0.035) independent of the same confounders. When replacing waist circumference with BMI in the models, hypertension retained its association with lower myocardial function, whereas the association with abnormal LV geometry was attenuated. Conclusion: In participants with increased BMI without known clinical cardiovascular disease, concomitant hypertension was associated with lower systolic myocardial function and more abnormal LV geometry. Clinical trial registration: URL: http://www.clinicaltrials.gov NCT02805478.